Find the sum of all positive integers
x
such that for some positive integer
y
,
x
y
+
x
−
y
=
1
0
0
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
subtracting 1 on both sides we get: ( x − 1 ) ( y + 1 ) = 9 9 Factors of 99 are 1, 3, 9, 11, 33, 99. However x − 1 can't be 99 since y will be 0. So x = 2 , 4 , 1 0 , 1 2 , 3 4 . Adding these values we get 62
Sorry I meant x+1 can't be 99, sorry for the typo :)
Log in to reply
Is there another typo that you should correct?
Log in to reply
Oh yeah, it's x-1, not x+1. Geez, what was I thinking!
I have a question: x=100 and y =0 is a solution to the equation isn't it?
Log in to reply
@José Marín Guzmán – However, it asks for positive integers, therefore the solution doesn't work
Suppose we find the value of x in terms of y . In doing this, we will find out that x=1+ y + 1 9 9
Consider from y + 1 9 9
y+1 should be a factor of 99. So these are the possible positive values of y+1; 1,3,9,11,33,99 , which are the factors of 99
but if y+1=1, y=0 so 1 is omitted. So going to the 1st equation for x in terms of y. Just substitute the value of y+1 from the equation we can have the values of x.
Let N be the sum of positive integral value of x.
N=34+12+10+4+2 N=62
x y + x − y = 1 0 0 ⟹ x ( y + 1 ) = 1 0 0 + y . Let us say that for some x = k , y is a positive integer. This would mean, k ( y + 1 ) = 1 0 0 + y ⟹ k y + k = 1 0 0 + y ⟹ y ( k − 1 ) = 1 0 0 − k ⟹ y = k − 1 1 0 0 − k .
Since y is an integer, 1 0 0 − k ≡ 0 ( m o d k − 1 ) ⟹ 1 0 0 ≡ k ( m o d k − 1 ) . Let m + 1 = k for some m . This means 1 0 0 ≡ m + 1 ≡ 1 ( m o d m ) ⟹ 9 9 ≡ 0 ( m o d m ) .
The divisors of 9 9 are 1 , 3 , 9 , 1 1 , 3 3 , 9 9 . Therefore, all possible values of k are 2 , 4 , 1 0 , 1 2 , 3 4 , 1 0 0 . But, 1 0 0 does not work. So we exclude it. The sum of the rest is 6 2 , which is our answer.
i can't understand the step ky+k=100+y=> y(k-1)=1
Log in to reply
I'm sorry it should be k ( y − 1 ) .
Log in to reply
no..... u r right in your solution.... and good work..
sorry its my fault
Using Simon's Favorite Factoring Trick, we get xy-y+x-1=99 which means (x-1)(y+1)=99 which is a Diophantine Equation. Notice that x-1 can be 1, 3, 9, 11, or 33, but not 99 because then y=0 which is not positive. So those values of x-1 mentioned above give x=2, 4, 10, 12, or 34, and 2+4+10+12+34=62, our answer.
Simon's Favorite Factoring trick! I like that. From AoPS, right?
=(y*(x-1)+x=100) Only x even will be allowed because even + even = even and if x=odd then first term will get even and even + odd can never be even. Then Try and substitute all combo to get x=2,4,10,12,34
Problem Loading...
Note Loading...
Set Loading...
Using SFFT :
Substrating 1 from both sides, this can be factorized as:
( x − 1 ) ( y + 1 ) = 9 9
Since 99 is equal to: 3 2 ∗ 1 1
9 9 has ( 2 + 1 ) ∗ ( 1 + 1 ) = 6 divisors that are : ( 1 , 3 , 9 , 1 1 , 3 3 , 9 9 )
But when ( x − 1 ) = 9 9 , ( y + 1 ) = 1 which means that y is 0 and so we have to exclude it.
So finally x can be 2 , 4 , 1 0 , 1 2 , 3 4
And 2 + 4 + 1 0 + 1 2 + 3 4 = 6 2